Предмет: Математика,
автор: bekbosunovbeka
решите уравнение 3x-(x-3(x-2(x-1)))=0
Ответы
Автор ответа:
0
3х-(х-3(х-2(х-1)=0
3х-(х-3(х-2х+2)=0
3х-(х-3(-х+2)=0
3х-(х+3х-6)=0
3х-(4х-6)=0
3х-4х+6=0
-х+6=0
-х=-6
х=6
3х-(х-3(х-2х+2)=0
3х-(х-3(-х+2)=0
3х-(х+3х-6)=0
3х-(4х-6)=0
3х-4х+6=0
-х+6=0
-х=-6
х=6
Автор ответа:
0
спасибоо
Автор ответа:
0
3x-(x-3(x-2(x-1)))=0
3x-(x-3(х-2х+2))=0
3х-(х-3х+6х-6)=0
3х-х+3х-6х+6=0
-х=-6
х=6
3x-(x-3(х-2х+2))=0
3х-(х-3х+6х-6)=0
3х-х+3х-6х+6=0
-х=-6
х=6
Похожие вопросы
Предмет: Алгебра,
автор: artemchere777
Предмет: Геометрия,
автор: IIIuIIoBHuk
Предмет: Английский язык,
автор: vjoou
Предмет: Математика,
автор: Аноним
Предмет: Математика,
автор: Amir71